(untitled) (Bangladesh Journal of Medical Science, 2024)
Background The problem of developing the speed of movement and speed-strength qualities of sprinters can be solved by applying special exercises in artificially difficult training conditions. The purpose of the study is to explore the possibilities of using special training tools, in particular running in artificially difficult conditions at the stage of special physical training of sprinters of mass categories. Materials and methods: The study involved young men aged 17-19 years old in the number of 28 people who were engaged in sprint running in the athletics section at the sports school of the Olympic reserve of the city of Kirov (Russia). The pedagogical experiment began on November 5, 2022 and ended on May 24, 2023. By the method of random sampling, all athletes were differentiated into a control group that practiced according to the standard methodology for training sprinters in natural conditions of difficulty and an experimental group in which sprinters practiced in artificially created conditions of difficulty. When processing the results of the study, the Student’s T-test was used. Results After the end of the pedagogical experiment, the indicators in both groups improved. The sprinters from the control group had higher scores from 1% to 3% in all tests (p>0.05). In the athletes from the experimental group, from the beginning to the end of the study, the indicators improved from 4.5% to 5.9% on all tests (p<0.05). This proves the effectiveness of using a set of exercises and load components in working with athletes in artificially created difficult exercise conditions. Conclusion: If you use a special set of exercises in artificially created difficult conditions when working with sprinters aged 17-19, then the indicators of speed and strength abilities and speed of movement will significantly improve in comparison with athletes who train in natural conditions of difficulty. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page : 368-376